«УЧИТЬСЯ, ЧТО ЕСТЬ ЧЕЛОВЕК И ЖИЗНЬ» («ЗАПИСКИ ИЗ МЕРТВОЕО ДОМА» Ф. М. ДОСТОЕВСКОЕО) - Базилевская, Азлита (Acta Neophilologica, 2007)
"Notes from the Dead House" belong to the "camp prose" with expressive-psychological dominant. Constant Dostoyevsky’s absorption into the problem of human shows itself here through close attention paid to the solution of "human’s mystery", the quest for "human inside human". The general idea of artistic construction of this work is the movement from initial impressions towards discovery of the hidden gist. The writer aspires to comprehend human nature individual manifestations and general principles. The main motif of "Notes" - "I want to be a human" - is the result of his searching for the truth about a human being.